Pengembangan Media Pembelajaran Video Animasi Berbasis Powtoon pada Mata Pelajaran Teknologi Perkantoran Kelas X SMK Satya Bhakti 2 Jakarta - Ni Ketut Sapta Ningrum; Roni Faslah; Darma Rika Swaramarinda (Syntax Corporation Indonesia, 2024)
This study aims to develop video-based interactive learning media using the Powtoon application for Office Technology lessons in class X SMK Satya Bhakti 2 Jakarta. The method used in this research is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The evaluation results show that the developed learning media is very feasible to use, with an average score of 92.17% from media experts and 96.19% from material experts, both of which fall into the category of ‘Very Feasible.’ This research is expected to increase the effectiveness of learning and attract students' interest in understanding the subject matter.